Exposure to the Organophosphate Pesticide Fenitrothion Directly Induced Defects in Mouse Embryonic External Genitalia. (11th August 2022) - Acebedo, Alvin R; Alcantara, Mellissa C; Nakanishi, Tsuyoshi; Ogawa, Takehiko; Yamada, Gen; Suzuki, Kentaro
Abstract: Many industrial chemicals have been reported as antiandrogenic substances. Exposure to these substances represents a potential risk to human health, particularly to the development of reproductive organs such as embryonic external genitalia (eExG). Currently, there is a need for more assay systems that can elucidate the toxicological actions and mechanisms of endocrine-disrupting chemicals. In this study, we show that the eExG slice culture assay is useful for the evaluation of the differing modes of action of endocrine-disrupting chemicals on urethra formation. We assessed the possible endocrine-disrupting activity of 3 chemicals with reported antiandrogenic function, diazinon, dibutyl phthalate, and fenitrothion (FNT) on eExG slices. Exposure to FNT, but not diazinon and dibutyl phthalate, induced defects of androgen-induced urethral masculinization and reduced expression of the androgen-target gene Mafb . Live imaging analyses showed that FNT treatment inhibited androgen-dependent MAFB induction within 12 h. Furthermore, FNT-treated tissue slices showed reduced expression of the androgen receptor. These results indicate that FNT disrupts androgen signaling by reduction of androgen receptor expression during androgen-induced eExG masculinization. This study thus highlights the importance of animal models, which allow for the effective assessment of tissue-specific endocrine-disrupting activity to further reveal the etiology of chemical-induced congenital anomalies.